IMPLIKASI NEGATIF DALAM PEMILIHAN KEPALA DAERAH SECARA LANGSUNG TERHADAP PENANGANAN PERKARA KORUPSI YANG MELIBATKAN KEPALA DAERAH - KARTIKA DEWI IRIANTO, SH, MH ANDREAS RONALDO, SH, MH (Menara Ilmu, 2016)
Negative implications in the area of direct election of the Head of the handling of corruption cases involving the head area. Based on the research that has been done in the search for answers to the problems that have been formulated, it is concluded as follows: Negative implications of direct election of regional head of the handling of corruption cases involving the head of the region is the number of actors involved in an act of corruption involving the head of the region, which started from giving donors during the campaign and during the local elections directly. Thus the law enforcement officers get a big obstacle to unravel the corruption cases involving local leaders to completion. It is caused by a number of related parties. Thus, in the handling of corruption involving the head of the frequent presence of sacrificial structural officers only while the head of the region can still be argued.Keyword: Elections Directly, Regional Head, corruption